Thoughts and beliefs of healthcare workers regarding the coronavirus disease 2019 (COVID-19) vaccine and which messaging themes might affect vaccine confidence and recommendation of the vaccine - S. Shaefer Spires; Jenna L. Clark; Rebecca Rayburn-Reeves; Elizabeth Dodds Ashley; Avani Desai; Jan Lindemans (Cambridge University Press, 2022)
We surveyed healthcare workers within the Duke Antimicrobial Stewardship Outreach Network (DASON) to describe beliefs regarding coronavirus disease 2019 (COVID-19) vaccination and their decision-making process behind vaccination recommendations. In contrast to the type of messaging that appealed most on a personal level to the healthcare workers, they preferred a more generic message emphasizing safety and efficacy when making vaccination recommendations.